Molecular Structure and Decomposition Kinetics of Kaolinite/Alkylamine Intercalation Compounds - Zhou, Yi; Liu, Qinghe; Xu, Peijie; Cheng, Hongfei; Liu, Qinfu (Frontiers in Chemistry, 2018)
Although the development of clay/polymer nanocomposites and their applications have attracted much attention in recent years, a thorough understanding of the structure and the de-intercalation mechanism of clay/polymer nanocomposites is still lacking. In this study, the intercalation of kaolinite (Kaol) with alkylamine was investigated by X-ray diffracion (XRD), Fourier-transform infrared spectroscopy (FTIR), and thermogravimetry and differential scanning calorimetry (TG-DSC). The results showed that the intercalation of Kaol/methanol compound with hexylamine (HA), dodecylamine (DA), and octadecylamine (OA) led to the expansion of the interlayer distance and resulted in the dominant basal diffraction at 2.86, 4.08, and 5.66 nm. The alky chains of HA, DA, and OA are tilted towards the Kaol surface in bilayer with an inclination angle of approximately 40°. The most probable mechanism functionm, activation energy E, and pre-exponential factor A were obtained by mutual authentication using the KAS and Ozawa methods, itrative and Satava integral method. The average activation energy E of the three intercalation compounds, Kaolpi/HA, Kaolpi/DA, and Kaolpi/OA are 104.44 kJ mol-1, 130.80 kJ mol-1, and 154.59 kJ mol-1, respectively. It shows a positive correlation with the alkyl chain length. The pre-exponential factor A was estimated to be 1.09×1015 s-1, 1.15×108 s-1, and 4.17×1021 s-1, respectively. The optimized mechanism function for the de-intercalation of alkylamine is G(α) = [(1-α) -1/3-1] 2.